MENGENAL FILSAFAT ANTARA METODE PRAKTIK DAN PEMIKIRAN SOCRATES, PLATO DAN ARISTOTELES - Mahfud; Patsun (CENDEKIA: Jurnal Studi Keislaman, 2019)
Philosophy as the parent of all science is an important study that needs to be studied, the goal is that the deepest meaning in the context of thinking becomes clearer. So that inevitably philosophical studies need to be introduced in various forms. In a more explicit context that philosophy is an attempt to invite humans to be able to use the potential of extraordinary extraordinary intelligence is able to reveal all the deepest meanings of every inch of scientific analysis that has become knowledge. In this context philosophy as a field of contemplation which leads to ways to discover the nature of what is called love of wisdom can lead us to maturity of thought so that in time it will arrive at the desired essence in philosophy. Furthermore, to find out how to achieve the essence of philosophy is by trying to recognize the method of the Systematic Method: we are known as the work of philosophy or the contents of the first philosophy (essence theory or we are familiar with the term ontology). Second is (our theory of knowledge is also familiar with the term epistemology). Third is (value theory and known as axiology). Historical Method, Critical method: this method is used by Socrates and Plato. Intuitive Method: this method is used by Plotinos and Bergson. Scholastic Method: this method was used by Aristotle and Thomas Aquinas in the Middle Ages. And next is to know other characteristics such as history, and the thoughts of the characters.